Dundee Annual Neurosurgery Skills Event (DANSE)—Improving the Availability and Affordability of Neurosurgical Skills Workshops for Medical Students - Hutton, Dana; Ashraf, Mohammed; Sescu, Daniel; Ismahel, Hassan; Hepburn, Katie; Lumsden, Emma; Wright, Poppy; Chai, Carmen; Helley, Michael; McSorley, Nathan; Mohamed, Belal; Abdulrahman, Mohammed; Page, Beverley; Porter, Roslyn; Bodkin, Peter; Okasha, Mohamed (Asian Journal of Neurosurgery, 2024)
Background Neurosurgery can be a daunting career choice for medical students, with preparation for trainee application often being inaccessible and expensive. This article describes a student-led neurosurgical skills event supported by local neurosurgery faculty members. Such event was designed to offer a means to bridge this gap by providing an opportunity to practice neurosurgical techniques in simulation, and learn about what a career in neurosurgery involves.Methods Pre- and postskills laboratory surveys were used to ascertain the baseline confidence and knowledge of common neurosurgical techniques, as well as to what both the application to neurosurgery and the typical workload of a neurosurgeon involves. The conference offered six neurosurgical workshops as well as three lectures to provide practical and theoretical learning opportunities. The session included introduction to the candidates and faculty, identification of learning objectives, and career discussion. Postcourse feedback also was also used to assess learning outcomes.Results Eighteen students attended the event. Postskills event, students were significantly more likely to understand the principles behind all of the relevant neurosurgical skills included on the day. Additionally, students were more likely to understand what a career in neurosurgery involves, and how to approach applying for a training number. Respondents enjoyed the workshops, valued hands-on experience and interactions with consultants, found it affordable, and would recommend to their peers.Conclusions For medical students interested in a career in neurosurgery, opportunities to learn relevant techniques and skills are often expensive and difficult to come across. Here, we highlight affordable methods of simulation to result in significant student satisfaction. Additionally, providing ample opportunity to practice different neurosurgical techniques under almost 1:1 level tutoring enables significant increases in students' confidence and understanding of different neurosurgical concepts. We greatly encourage other medical student groups to develop their own hands-on simulation events to attract medical students to a surgical field often considered daunting and inaccessible, and address gaps in the medical school curriculum.
Keywords: medical education; simulation teaching; accessibility; neurosurgical skills; medical student